-2t-6=-t

Simple and best practice solution for -2t-6=-t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2t-6=-t equation:



-2t-6=-t
We move all terms to the left:
-2t-6-(-t)=0
We add all the numbers together, and all the variables
-2t-(-1t)-6=0
We get rid of parentheses
-2t+1t-6=0
We add all the numbers together, and all the variables
-1t-6=0
We move all terms containing t to the left, all other terms to the right
-t=6
t=6/-1
t=-6

See similar equations:

| 9x+6x=7 | | 6-6x+42+7=0 | | 1-9v=-9v+4v+9 | | y/5+4=y/4 | | 5×-3.2=z | | (-s+8)+(7s+2)=2(-6s+23) | | 6s+2-4=10 | | -3.2×5=v | | F(1/2)=2x+1 | | 4r+10=6r-6 | | 7(2+6x)=-231 | | 0.05x+0.10(15-x)=0.90 | | 8z-3=4(z-3)+9+4+z | | -6(h+3)=-36 | | 15c=-30 | | (-p+71)+(3p-59)=2(-p+86) | | 9-b=3b-7 | | (2x-3)/4+x=(2x+3)/2+8 | | 8z-3=4(2-3)+9+4z | | 6-2/5=n | | x+2x+1/2(3x)=3 | | 5^2+10+20=y | | 3(w-4)-8=-6(-4w+5)-7w | | Y=-100x+800 | | 4x-0=17 | | 15x-7x=8 | | 10.3-x/18=5x-0.3/38 | | (-5)−5y=−15 | | 0=-16x^2+80x+6 | | 0-3y=17 | | 2x+14=6x+10 | | -4x+6+3x=10-3x+4 |

Equations solver categories